The team unbound: unpacking the real implications of the shift to global, dynamic, and overlapping teams - Mortensen, Mark (Henry Stewart Talks, 2013)
Overview, What we know, A core question, Changing global context, Changing nature of teams, Boundary fluidity and its effects, Boundary multiplexity and its effects, Why does it matter if teams are less well-bounded, Rethinking boundedness as a variable